Proposed diagnostic criteria and classification for Laugier-Hunziker Syndrome - Mishra, Neha (Journal of Chitwan Medical College, 2020)
Laugier-Hunziker syndrome is one of those rare syndromes which has yet not been reviewed and reported much in literature. So far, there is no diagnostic criteria and classification that can help with prompt diagnosis of this syndrome. In this article an attempt has been made to put forward a simple criterion along with a classification that can assist the practitioners with early detection and also will have substantial contribution in medical curriculum.